2009
DOI: 10.1099/mic.0.022731-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of iron-responsive proteins expressed by Chlamydia trachomatis reticulate bodies during intracellular growth

Abstract: The obligate intracellular bacterium Chlamydia trachomatis serovar E is the most prevalent cause of bacterial sexually transmitted disease. With an established requirement for iron, the developmental cycle arrests at the intracellular reticulate body stage during iron restriction, resulting in a phenomenon termed persistence. Persistence has implications in natural infections for altered expression of virulence factors and antigens, in addition to a potential role in producing chronic infection. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 48 publications
3
36
0
1
Order By: Relevance
“…The inhibition of NME causes cell cycle arrest in tumor cells (Yeh et al, 2000;Zhang et al, 2000), developmental defects (Boxem et al, 2004;Yeh et al, 2006), and early senescence in plants (Ross et al, 2005). Accordingly, recent data have also suggested that the expression of NME enzymes is tightly regulated throughout development, in response to abiotic stress and tumorigenesis (Selvakumar et al, 2006;Dill et al, 2009), suggesting that the fraction of proteins undergoing NME may vary over space and time. Despite the demonstration that this process is essential in all organisms and its identification as a valuable target for the design of new antibacterial and anticancer agents, the molecular mechanism underlying the physiological requirement for NME function in living cells remains largely unknown.…”
Section: Discussion Partial Retention Of the N-terminal Met Of Cytosomentioning
confidence: 99%
“…The inhibition of NME causes cell cycle arrest in tumor cells (Yeh et al, 2000;Zhang et al, 2000), developmental defects (Boxem et al, 2004;Yeh et al, 2006), and early senescence in plants (Ross et al, 2005). Accordingly, recent data have also suggested that the expression of NME enzymes is tightly regulated throughout development, in response to abiotic stress and tumorigenesis (Selvakumar et al, 2006;Dill et al, 2009), suggesting that the fraction of proteins undergoing NME may vary over space and time. Despite the demonstration that this process is essential in all organisms and its identification as a valuable target for the design of new antibacterial and anticancer agents, the molecular mechanism underlying the physiological requirement for NME function in living cells remains largely unknown.…”
Section: Discussion Partial Retention Of the N-terminal Met Of Cytosomentioning
confidence: 99%
“…Bacteria avoid the detrimental effects of iron by limiting its availability, restricting uptake, and sensing adequate iron levels (Clarke et al, 2001). In addition, new findings report that C. trachomatis responds to limited iron availability by increasing expression of proteins involved in protection against oxidative damage (Dill et al, 2009). C. pneumoniae protein levels under iron-limited conditions have also been examined, showing that iron stress induced observable changes in expression in at least six proteins (Wehrl et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Desferal was previously documented to reduce the epithelial cell intracellular ferritin level significantly (Dill et al, 2009). Protein samples from both cell culture growth conditions were removed throughout the chlamydial developmental cycle (0, 24, 36, 48, 60 and 72 hp.i.…”
Section: Increase In Ytga Concentration By Iron Restrictionmentioning
confidence: 99%
“…The endonucleolytic reaction performed by the RNAP catalytic center is slow, but is greatly stimulated by transcript cleavage factors including GreA (Fish and Kane, 2002;Sergei et al, 2005;Stepanova et al, 2007). A recent study of iron induced persistence in C. trachomatis E showed that both NusA and NusG were regulated (Dill et al, 2009). This study is intriguing as it shows that Nus factors are regulated during persistence and might explain why CTIG643 shows such discrepancy in termination under normal and stress conditions.…”
Section: Ncrna Expression Under Both Normal and Stress Conditionsmentioning
confidence: 99%